Beyond Foot-Dragging: A Reflection on the Reluctance of South Africa’s National Prosecution Authority to Prosecute Apartheid Crimes in Post-Transitional Justice - Konanani Happy Raligilia (Obiter, 2020)
To this day, apartheid is still regarded as one of the most heinous crimes to have affected humankind. The brutality of the apartheid system and its impact not only left devastating effects in the minds of the black majority who were affected by the system, but also drew international attention. This prompted the United Nations Security Council to pass drastic resolutions to try and end the apartheid system. It is important to highlight that apartheid crime was committed at the behest of the-then National Party government at the expense of the black majority. The attainment of democratic rule in 1994 also saw the emergence of the need for transitional justice. However, after 25 years of foot-dragging, the National Prosecution Authority in South Africa has still not been fully committed to prosecute apartheid atrocities. This article examines the crime of apartheid and the impact of the transitional justice process in South Africa. The article further reflects on the National Prosecution Authority’s reluctance to prosecute crimes of apartheid and examines the final report of the People’s Tribunal on Economic Crimes in South Africa.